Hierarchical Healthcare Facility Location at the Subdistrict Level in Western Uttar Pradesh: A Heuristic Approach - Verma, Prashant; Datta, Subhash (Advances in Social Sciences Research Journal, 2021)
The Governments across the world are making continuous efforts to attain health for all. The efforts can gain more efficiency if the new healthcare facilities are created at optimal locations. There are various constraints on healthcare facilities, like cost of setup, coverage distance, service distance, population load, manpower and services offered. These constraints operate in a complex setting giving rise to alternate scenarios. The study proposes replicable heuristics to obtain the optimal locations under alternate scenarios for the Sub Centers (SC), Primary healthcare centers (PHC) and Community healthcare centers (CHC). The study takes the case of a block of villages in most populous state of India using the publicly available data, data from census, government portals and Bing Maps services. The study generates several alternatives scenarios for maximize demand, minimize service distance and minimize total costs for different population covered and service distance. The methodology suggested here might be helpful for the location decision making at the block level by the district administration.